The Interaction of Fungicide and Nitrogen for Aboveground Biomass from Flag Leaf Emergence and Grain Yield Generation under Tan Spot Infection in Wheat - Matías Schierenbeck; María Constanza Fleitas; María Rosa Simón (Plants, 2023)
Pyrenophora tritici-repentis (Died.) Drechs., the causal agent of tan spot, is one of the most serious biotic diseases affecting wheat worldwide (Triticum aestivum L.). Studying the interaction between different fungicide mixtures and nitrogen (N) rates under tan spot outbreaks is of key importance for reducing aboveground biomass and grain yield losses. Taking this into account, our study took a mechanistic approach to estimating the combined effect of different fungicides and N fertilization schemes on the severity of tan spot, green leaf area index, SPAD index, aboveground biomass dynamics, and yield in a wheat crop affected at the reproductive stage. Our results indicated that reductions in green leaf area, healthy area duration (HAD), and the chlorophyll concentration (SPAD index) due to increases in the percentage of damage led to decreases in biomass production (−19.2%) and grain yield (−48.1%). Fungicides containing triazole + strobilurin + carboxamides (TSC) or triazole + strobilurin (TS) combined with high N doses showed the most efficient disease control. The positive physiological effects of TSC fungicides, such as extending the green leaf area, are probably responsible for the greater production of aboveground biomass (+29.3%), as well as the positive effects on grain yield (+15.8%) with respect to TS. Both fungicide treatments increased grains per spike, kernel weight, spikes m−2, grains m−2, and grain yield. The increase in biomass in the TSC tended to cause slighter non-significant increases in grains per spike, 1000-kernel weight and grain yield compared with TS. The linear regression revealed positive associations among the extension of HAD and biomass (+5.88 g.m−2.HAD−1.day−1), grain yield (+38 kg.ha.HAD−1.day−1), and grain number (100.7 grains m2.HAD−1.day−1), explained by the interactions of high N doses and fungicides. Our study is the first report of the positive effect of TSC fungicides with high N doses on grain yield related-traits under tan spot infections in wheat.